Hippocampal and prefrontal cortical NMDA receptors mediate the interactive effects of olanzapine and lithium in memory retention in rats: the involvement of CAMKII-CREB signaling pathways. - Amiri, Shiva; Jafari-Sabet, Majid; Keyhanfar, Fariborz; Falak, Reza; Shabani, Mohammad; Rezayof, Ameneh (Psychopharmacology, 2020)
Rationale: Treatment of bipolar disorder (BPD) with lithium and olanzapine concurrent administration is a major medicine issue with the elusive neurobiological mechanisms underlying the cognitive function. Objective: To clarify the precise mechanisms involved, the possible role of the hippocampus (HPC) and prefrontal cortical (PFC) NMDA receptors and CAMKII-CREB signaling pathway in the interactive effects of lithium and olanzapine in memory consolidation was evaluated. The dorsal hippocampal CA1 regions of adult male Wistar rats were bilaterally cannulated and a step-through inhibitory avoidance apparatus was used to assess memory consolidation. The changes in p-CAMKII/CAMKII and p-CREB/CREB ratio in the HPC and the PFC were measured by Western blot analysis. Results: Post-training administration of lithium (20, 30, and 40 mg/kg, i.p.) dose-dependently decreased memory consolidation whereas post-training administration olanzapine (2 and 5 mg/kg, i.p.) increased memory consolidation. Post-training administration of certain doses of olanzapine (1, 2, and 5 mg/kg, i.p.) dose-dependently improved lithium-induced memory impairment. Post-training administration of ineffective doses of the NMDA (10−5 and 10−4 μg/rat, intra-CA1) plus an ineffective dose of olanzapine (1 mg/kg, i.p.) dose-dependently improved the lithium-induced memory impairment. Post-training microinjection of ineffective doses of the NMDA (10−5 and 10−4 μg/rat, intra-CA1) dose-dependently potentiated the memory improvement induced by olanzapine (1 mg/kg, i.p.) on lithium-induced memory impairment which was associated with the enhancement of the levels of p-CAMKII and p-CREB in the HPC and the PFC. Post-training microinjection of ineffective doses of the noncompetitive NMDA receptor antagonist, MK-801 (0.0625 and 0.0125 μg/rat, intra-CA1), dose-dependently decreased the memory improvement induced by olanzapine (5 mg/kg, i.p.) on lithium-induced memory impairment which was related to the reduced levels of HPC and PFC CAMKII-CREB. Conclusion: The results strongly revealed that there is a functional interaction among lithium and olanzapine through the HPC and the PFC NMDA receptor mechanism in memory consolidation which is mediated with the CAMKII-CREB signaling pathway.